(untitled) (Географический вестник=Geographical bulletin, 2017)
Представлены результаты инвентаризации памятников природы окрестностей г. Красноуфимска. Дана оценка современного состояния растительного покрова этих ООПТ. CURRENT STATE OF NATURE RESERVES IN THE VICINAGE OF KRASNOUFIMSK CITY The phytodiversity of natural reserves in the vicinity of Krasnoufimsk at the florist and cenotic levels is revealed. Seven species of plants, which are included in the Red Book of Sverdlovsk region since 2008, are found. Assessment of the current state of especially protected natural areas had been based on the index of synanthropization, which varies from 3 to 21% in the studied communities.